Determinants of Consumer Purchase Intentions in Cleaning Product Refill Facilities as an Alternative to Reducing Single-use Plastic Packaging Waste - Puspita, Marissa Puspita; Nurcahyo, Rahmat Nurcahyo; Gabriel, Djoko S. Gabriel (JURNAL TEKNIK INDUSTRI, 2024)
Single-use plastic packaging is widely used in FMCG (Fast Moving Consumer Goods) to pack products.The use of single-use plastic packaging has become a daily habit and triggers an increasement of theamount of plastic waste. Nowadays, a linear economy has been swift into a circular economy to savethe environment. One of the best solutions is by providing household cleaning product refill facilitiesin several areas. Also, this research wants to find the influence of household cleaning product refillfacilities in order to reduce single-use plastic packaging waste. The Theory of Planned Behavior(TPB) is used in this research to analyze and estimate people's behavior. The questionnaires werecollected from potential customers and consumers who will or have refilled their liquid body wash atthe filling facility, especially in DKI Jakarta region. Also, this research helps to identify the impact ofenvironmental consciousness, environmental knowledge, subjective norms, and green marketing onthe purchase intention to refill cleaning products at filling facilities. The data obtained were thentested using Spearman's correlation and multiple linear regression tests. The result of this researchshows that the purchase intention to refill cleaning products at filling facilities is influenced by eachvariable of the research. Therefore, innovative refill cleaning products at filling facilities can be asolution to reduce the increase in plastic waste.